2011
DOI: 10.1063/1.3664141
|View full text |Cite
|
Sign up to set email alerts
|

Mass measurements near the Z = N line with JYFLTRAP

Abstract: Masses of nuclides involved in astrophysical rp and ν p processes have to be known precisely in order to model these processes reliably. Mass excesses for 90 ground state and 8 isomeric states of neutron-deficient nuclides have been determined with a precision of better than 10 keV with the JYFLTRAP double Penning trap mass spectrometer at the Ion-Guide Isotope Separator On-Line facility in Jyväskylä. Highlights of the measurements related to nuclear astrophysics are given. Some of the measured isomers, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Like L. reuteri DSM 17938, its binding plateaus to its maximum relatively easily, reaching half maximum adhesion at OD A50 17.7 (Table 1). It has been suggested that biofilm-like aggregation is necessary for EcN colonization 72 and that mucoadhesion is influential in initial binding before other competitive mechanisms take over. Additionally, compared to pathogenic strains, commensal E. coli have more flexibility in their ability to perform metabolic shifts depending on the mono-and disaccharide carbon sources available from mucin glycans 73 .…”
Section: Different Probiotics Display Vastly Different Mucoadhesive Cmentioning
confidence: 99%
“…Like L. reuteri DSM 17938, its binding plateaus to its maximum relatively easily, reaching half maximum adhesion at OD A50 17.7 (Table 1). It has been suggested that biofilm-like aggregation is necessary for EcN colonization 72 and that mucoadhesion is influential in initial binding before other competitive mechanisms take over. Additionally, compared to pathogenic strains, commensal E. coli have more flexibility in their ability to perform metabolic shifts depending on the mono-and disaccharide carbon sources available from mucin glycans 73 .…”
Section: Different Probiotics Display Vastly Different Mucoadhesive Cmentioning
confidence: 99%